The dorsal hippocampal protein targeting to glycogen maintains ionotropic glutamate receptor subunits expression and contributes to working and short-term memories in mice - Yuki Kambe (Elsevier, 2022)
Brain glycogen metabolism is known to be involved in the learning and memory processes. Protein targeting to glycogen (PTG) is a crucial molecule for glycogenesis, and its expression level is shown to be increased in the dorsal hippocampus during fear memory acquisition and recall, suggesting that PTG may contribute to the memory process. However, its detailed role in the dorsal hippocampus remains unclear. Therefore, we knocked down the expression of PTG in the dorsal hippocampus and attempted to analyze its function behaviorally. PTG expression was found to be enriched in astrocytes. Furthermore, short hairpin RNA against PTG suppressed the expression of PTG in astrocytes. Mice with knockdown of PTG in the dorsal hippocampus showed suppressed alternation behavior in the Y-maze test and reduced memory recall at the first hour after acquisition in the passive avoidance test. Knockdown of mouse dorsal hippocampal astrocyte-specific PTG also impaired working memory in the Y-maze test. GluR1, GluR2, and NR2a subunits expressions were significantly down-regulated in the dorsal hippocampus of mice in which PTG was knocked down. These results indicate that PTG in the dorsal hippocampal astrocytes may contribute to working and short-term memories by maintaining the expression of glutamate receptor subunits.